FINANCIAL INCLUSION OF MSMES THROUGH SHARIA CROWDFUNDING - Bunga Dwi Fani Ritonga; Saparuddin Siregar; Maryam Batubara (SOSIOEDUKASI, 2025)
This study aims to analyze the development of Islamic crowdfunding as an alternative financing instrument for Micro, Small, and Medium Enterprises (MSMEs) and its challenges in strengthening financial inclusion within Indonesia’s Islamic economic ecosystem. The research focuses on examining the dynamics of Sharia-based crowdfunding platforms, their regulatory framework, the implementation of Sharia principles, and the challenges faced by MSMEs in accessing digital financing. A qualitative approach was employed through in-depth interviews with academics, practitioners, and Islamic finance experts, supported by secondary data from industry reports, OJK regulations, and relevant literature. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings show that Islamic crowdfunding has grown significantly as a response to the limited access of MSMEs to formal financial institutions. Platforms such as Ammana and Santara play an important role in facilitating Sharia-compliant financing through profit-sharing contracts such as mudharabah and musyarakah. National statistics indicate strong market growth, with Sharia-based securities crowdfunding accounting for 52.1% of total SCF funding in 2024. However, several challenges persist, including low Sharia literacy, limited digital skills among MSMEs, regulatory inconsistencies, and gaps in technological infrastructure. The study concludes that Islamic crowdfunding contributes meaningfully to MSME financial inclusion and supports the expansion of Indonesia’s Islamic economic sector. To optimize its impact, stronger regulatory harmonization, continuous literacy programs, technological improvement, and stakeholder collaboration are required to enhance trust, accessibility, and Sharia compliance.